Peripheral Calcifying Odontogenic Cyst: A Case Report and Review of the Literature - Resende, Renata Gonçalves (Springer US, 2010)
The peripheral calcifying odontogenic cyst (PCOC) accounts for less than 25% of the cases of calcifying odontogenic cysts and most commonly appears as a nodule on the gingiva. This paper aims to present both a case report of a PCOC located in the left vestibular maxilla as well as a review of the English-language literature. An 11-year-old female patient presented a swelling in the vestibular region of teeth 12 and 13. Periapical and panoramic radiographs demonstrated irregular calcification. Surgical excision was performed. Microscopic examination showed an odontogenic cystic lesion lined by ameloblastoma-like epithelium, containing numerous ghost cells. Areas of calcification associated with ghost cells could also be observed. The patient was diagnosed with PCOC. The patient has been disease-free for 36 months. The review of the cases of PCOC showed 44 well-defined cases. The mean age was of 49.4 years at the time of diagnosis. The reported cases appeared as a painless swelling, with a slight predilection for females, and were more frequently located in the anterior region of the maxilla or mandible. Surgical excision is the treatment of choice, and recurrence is rare.